Electron Energy Loss Processes in Methyl Methacrylate: Excitation and Bond Breaking - Luxford, Thomas F M; Fedor, Juraj; Kočišek, Jaroslav (The journal of physical chemistry. A, 2023)
Details of electron-induced chemistry of methyl methacrylate (MMA) upon complexation are revealed by combining gas-phase 2D electron energy loss spectroscopy with electron attachment spectroscopy of isolated MMA and its clusters. We show that even though isolated MMA does not form stable parent anions, it efficiently thermalizes the incident electrons via intramolecular vibrational redistribution, leading to autodetachment of slow electrons. This autodetachment channel is reduced in clusters due to intermolecular energy transfer and stabilization of parent molecular anions. Bond breaking via dissociative electron attachment leads to an extensive range of anion products. The dominant OCH3- channel is accessible via core-excited resonances with threshold above 5 eV, despite the estimated thermodynamic threshold below 3 eV. This changes in clusters, where MnOCH3- anions are observed in a lower-lying resonance due to neutral dissociation of the 1(n, π*) state and electron self-scavenging. The present findings have implications for electron-induced chemistry in lithography with poly(methyl methacrylate).